The Experience of Employment Reforms and Unemployment Reduction under US President W. J. Clinton - Abdurasul A. Rozakov (Researchparks Publishing, 2023)
The article discusses the ways and methods of solving the problem of unemployment and reforms in the field of employment during the reign of US President W. J. Clinton